The Dutch Republic : its rise, greatness and fall, 1477-1806 - Israel, Jonathan Irvine (Clarendon Press, 1995)
The Dutch Golden Age - the age of Grotius, Spinoza, Rembrandt, Vermeer, and a host of other renowned artists and writers, was also remarkable for its immense impact in the spheres of commerce, finance, shipping, and technology. It was in fact one of the most spectacularly creative episodes in the history of the world. In this book, Jonathan Israel gives the definitive account of the emergence of the United Provinces as a great power, and explains its subsequent decline in the eighteenth century. He places the thought, politics, religion, and social developments of the Golden Age in their broad context, and examines the changing relationship between the northern Netherlands and the south, which was to develop into modern Belgium. One of the principal aims of the book is to provide a new type of integrated history which draws the different dimensions of the discipline firmly together in strictly non-technical language. The result is a comprehensive and lucid account as useful to the reader primarily interested in artistic and cultural history as to the student who needs a survey of the Republic's institutions, class structure, and economic development. At the same time it will provide an invaluable aid to scholars interested in new research and new interpretations.
Keywords: Netherlands -- History -- House of Habsburg, 1477-1556.; Netherlands -- History -- Eighty Years' War, 1568-1648.; Netherlands -- History -- 1648-1795.; Netherlands -- History -- Batavian Republic, 1795-1806.; Netherlands -- History.; Pays-Bas -- Histoire.; Pays-Bas -- Histoire -- 1477-1556 (Maison de Habsbourg); Pays-Bas -- Histoire -- 1568-1648 (Guerre de Quatre-Vingts Ans); Pays-Bas -- Histoire -- 1648-1795.; Pays-Bas -- Histoire -- 1795-1806 (République batave); HISTORY -- General.; Netherlands; Niederlande; Machtpolitik; Politik; Politisches System; Unabhängigkeitskrieg; Wirtschaft; Republiek der Verenigde Nederlanden.; Regions & Countries - Europe.; History & Archaeology.; Netherlands, Belgium & Luxembourg.; Pays-Bas -- 1795-1806 (République batave); Pays-Bas -- Civilisation.; Pays-Bas -- 17e siècle.; Pays-Bas -- 18e siècle.; HOLANDA -- HISTORIA -- CASA DE HABSBURG, 1477-1556.; HOLANDA -- HISTORIA -- GUERRAS DE LA INDEPENDENCIA, 1556-1648.; HOLANDA -- HISTORIA -- 1648-1795.; HOLANDA -- HISTORIA -- REPUBLICA BATAVIA, 1795-1806.; 1477-1806; History